2021
DOI: 10.3390/su13041757
|View full text |Cite
|
Sign up to set email alerts
|

Managers’ Competences in Private Hospitals for Investment Decisions during the COVID-19 Pandemic

Abstract: The COVID-19 pandemic has posed an unprecedented challenge for health systems worldwide. The increased demand for investment in hospitals has become one of the greatest financial vulnerabilities, and in this context, the manager’s involvement in decision-making is associated with better analysis in order to achieve better results. This article aims to define a model to outline the manager profile in private hospitals, as well as the process and the relationship with investment decision-making, so as to guide f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…Critical incident interviews [ 80 , 102 , 112 , 113 , 128 ] and behavioral event interviews [ 12 , 86 , 105 , 116 , 127 , 131 ] were also performed. Interviews were conducted online [ 115 ], by telephone [ 63 , 98 , 115 ], and face-to-face [ 10 , 11 , 39 , 58 , 79 , 86 , 109 , 114 , 120 , 125 ], both online and face-to-face [ 9 , 129 ], or both telephone and face-to-face [ 36 , 122 ]. Nine studies did not explicitly outline the form of interviews [ 20 , 66 , 74 , 97 , 103 , 104 , 107 , 108 , 126 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Critical incident interviews [ 80 , 102 , 112 , 113 , 128 ] and behavioral event interviews [ 12 , 86 , 105 , 116 , 127 , 131 ] were also performed. Interviews were conducted online [ 115 ], by telephone [ 63 , 98 , 115 ], and face-to-face [ 10 , 11 , 39 , 58 , 79 , 86 , 109 , 114 , 120 , 125 ], both online and face-to-face [ 9 , 129 ], or both telephone and face-to-face [ 36 , 122 ]. Nine studies did not explicitly outline the form of interviews [ 20 , 66 , 74 , 97 , 103 , 104 , 107 , 108 , 126 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies (n = 16 studies) mentioned that protocol including pre-determined open questions was developed to guide the interview process. Less than 40% of the studies (23 out of 69) provided adequate details on how interview questions were developed [ 11 , 12 , 29 , 61 , 86 , 93 – 96 , 98 , 99 , 103 , 109 , 111 , 115 , 117 , 121 , 123 , 124 , 129 , 131 , 132 ]. The following common methods were used to develop interview questions:…”
Section: Resultsmentioning
confidence: 99%
“…Several studies found that the perception of managers regarding the uncertainty of future earnings can affect corporate dividend policy [1,50,51]. Other studies found that firms have to adjust their corporate's policy such as corporate investment [52][53][54] and corporate dividend payout policy [55] in order to survive in the Covid-19 pandemic period. Suleman and Yaghoubi [56] studied the effect of pandemics through infectious disease equity market volatility index on corporation actions.…”
Section: B the Role Of Infectious Disease On Corporate Decisionsmentioning
confidence: 99%
“…The most interesting aspect to prepare employees who can accept change is part of management to provide an understanding of the change. If the understanding has been given, it is hoped that a positive attitude will emerge and be a factor in the success of organizational performance (Asbari et al, 2020;Marques et al, 2021). The implementation of health protocols at the medical record installation at RSAB Harapan Kita was in accordance with the circular issued by the National Association of Health Information Management Professionals (DPP PORMIKI); such as employees should wearing masks, cleaning hands with hand rubs or sanitizer after handling medical records, and practicing social distancing (Safitri et al, 2021).…”
Section: Kesansmentioning
confidence: 99%